EFEKTIFITAS PERAWATAN TERJADWAL PADA AIR CONDITIONING JENIS STANDING FLOOR DI BANDAR UDARA SULTAN HASSANUDIN - MAKASSAR - Kurniawati, Zulina; Astuti, Annisa Puji; Yuspin, Yosia; Azizi, Dimas Setia; Pradani Putri, Aulia Bilqis; Lestari, Endah Dwi (Jurnal Teknik Mekanikal Bandar Udara, 2023)
Air Conditioning (AC) Standing Floor is a type of cooler whose use is notaffixed to residential walls but placed on the floor. Air Conditioner (AC)is one type of electronic device that consumes quite a lot of time for therepair and maintenance process. Air Conditioning (AC) Standing Floorneeds to be maintained at a comfort level as a necessity for the comfort ofa room. AC component maintenance can make it last longer and the coldit produces is as needed. In order to have a long lifetime and reduce thecost of damage that occurs if there is no consistency in maintenance.Examination is carried out using an anemometer and stroboscope. Thepurpose of maintenance on the air conditioner is to smooth so that thereare no obstructions between the evaporator fins.